Clinical Perspectives on Colorectal Cancer Screening at Latino-Serving Federally Qualified Health Centers. (February 2015) - Coronado, Gloria D.; Petrik, Amanda F.; Spofford, Mark; Talbot, Jocelyn; Do, Huyen Hoai; Taylor, Victoria M.
Purpose. Colorectal cancer is the second most common cause of cancer death in the United States, and rates of screening for colorectal cancer are low. We sought to gather the perceptions of clinic personnel at Latino-serving Federally Qualified Health Centers (operating 17 clinics) about barriers to utilization of screening services for colorectal cancer. Method . We conducted one-on-one interviews among 17 clinic personnel at four Latino-serving Federally Qualified Health Center networks in Oregon. All interviews were recorded, transcribed, and coded, and themes were grouped by influences at three levels: the patient, the organization, and the external environment. Results . Estimated proportions of eligible patients who are underscreened for colorectal cancer ranged from 20% to 70%. Underscreening was thought to occur among low-income, underinsured, and undocumented patients and patients having multiple health concerns. Limited funding to pay for follow-up testing in patients with positive screens was cited as the key factor contributing to underscreening. Conclusions . We identified health care provider perceptions about the underutilization of screening services for colorectal cancer; our findings may inform future efforts to promote guideline-appropriate cancer screening.